Preparation and hydrogen storage properties of MgH2-trimesic acid-TM MOF (TM=Co, Fe) composites. Issue 10 (October 2019) - Ma, Zhewen; Zou, Jianxin; Khan, Darvaish; Zhu, Wen; Hu, Chuanzhu; Zeng, Xiaoqin; Ding, Wenjiang
Abstract: Two kinds of metal-organic frameworks (MOFs) based on Co (II) and Fe (II) as metal ions and trimasic acid (TMA) as organic linker were synthesized. They were used to prepare corresponding MgH2 -TM MOF (TM = Co, Fe) composites via ball-milling. X-ray diffraction analyses show the formation of Mg2 Co and α-Fe phases in MgH2 -TM MOF composites after decomposition. Both of the well dispersed Mg2 Co and α-Fe nanoparticles exhibit considerable catalytic efficiency in accelerating the sorption kinetics of MgH2 . The dehydrogenated MgH2 -Fe MOF composite shows faster hydriding kinetics than the pure MgH2 and MgH2 -Co MOF. Meanwhile, the apparent dehydrogenation activation energy ( E d ) of the MgH2 -Co MOF and MgH2 -Fe MOF composites are 151.3 ± 9.4 and 142.3 ± 6.5 kJ/mol H2, both of which are lower than that of pure MgH2 (181.4 ± 9.2 kJ/mol H2 ). The improvement on the sorption kinetics of the MgH2 -TM MOF powders is mainly attributed to the catalytic effects of nano-sized Mg2 Co and α-Fe formed on the surface of Mg/MgH2 particles.